Improved Derivatives of Bactenecin, a Cyclic Dodecameric Antimicrobial Cationic Peptide - Wu, Manhong (American Society for Microbiology, 1999)
Both linear and cyclic derivatives of the cyclic 12-amino-acid antimicrobial peptide bactenecin were designed based on optimization of amphipathicity and charge location. In general, increasing the number of positive charges at the N and C termini and adding an extra tryptophan residue in the loop not only increased the activities against both gram-positive and gram-negative bacteria but also broadened the antimicrobial spectrum.